Agile Method for Web-Based Meeting Room Reservation Case Study at: RSUD dr. Haryoto Lumajang - Inggrid Yanuar Risca Pratiwi; Hendra Pradibta; Yoppy Yunhasnawa; Aldi Nur Fahmi; Mochammad Calvin Rozil Hufron Kholil (Department of Informatics Engineering, 2026)
RSUD dr. Haryoto Lumajang, provides various supporting facilities, including meeting rooms for coordination, evaluation, and official meetings. However, the manual reservation process using Microsoft Excel and verbal requests often leads to scheduling conflicts, overlapping reservations, recording delays, miscommunication, and a lack of transparency regarding room availability. These inefficiencies reduce administrative effectiveness and user satisfaction. This study aims to design and develop a web-based meeting room reservation system using the Agile method, which emphasizes collaboration, flexibility, and iterative development to align the system with institutional needs. The system was implemented using the Laravel framework and MySQL database, focusing on reservation, verification, and archiving features. The testing results show that the system successfully improves accuracy by reducing manual input errors, provides real-time availability checks to avoid conflicting schedules, and enables administrators to manage reservations more efficiently. Additionally, the system includes a dedicated column for consumption needs, allowing clearer information management and minimizing miscommunication between users and administrators. Overall, the system enhances transparency, accelerates the booking process, and supports structured data management. Future development is recommended to include a visual calendar feature for room availability and continuous improvements to ensure greater usability, adaptability, and user comfort in meeting room reservation at RSUD dr. Haryoto Lumajang.